Cluster analysis to profile socioeconomically disadvantaged students and their impact on academic performance - Li, JiZhi; Chong, Sylvia (Advances in Social Sciences Research Journal, 2022)
Several studies have highlighted the underperformance of the Malay community in Singapore. This community had not progressed as well as the other ethnic groups in both socio-economic terms as well as in their academic performances Their academic performances in milestone educational examinations are below national rates. A tuition scheme organised by a Malay community social service group, was established to support the Malay students learning. This paper reports the findings of a cluster analysis that was used to explore how the students’ profile is associated with their academic performance. This study is part of a wider project that employed analytics to generate insights to improve the teaching and learning of socioeconomically disadvantaged Malay students.